Investigating the Trichosanthis Pericarpium - Trichosanthis Radix herbal pair’s role in alleviating COPD through gut microbiota function, metabolomics analysis and cell validation experiment - Yushan Zhao; Xiaoying Tan; Tian Wang; Yuxuan Yuan; Kelei Su; Erxin Shang; Qingling Xiao; Sheng Guo; Shulan Su; Huangqin Zhang; Jin-ao Duan; Pei Liu (PLoS ONE, 2025)
The herbal pair of Trichosanthis Pericarpium – Trichosanthis Radix (TP-TR) is derived from the classic prescription Bei-Mu-Gua-Lou-San in Yixue Xinwu, which is commonly used to treat lung heat and cough. Both originate from Trichosanthes kirilowii Maxim, a medicinal plant known for its effects to clear heat, dissolve phlegm, promote salivation, and relieve dryness. However, the compatibility, pharmacological synergy and gut-lung axis regulation mechanisms of TP-TR remain unclear. This study innovatively explores the therapeutic effects and underlying mechanisms of TP-TR in COPD through microbiome and amino acid metabolism. A COPD rat model was established to evaluate the efficacy of TP-TR. The gut microbiota was analyzed with 16S rRNA sequencing, while the metabolites in serum and lung were analyzed by UPLC-MS/MS. Functional prediction of the microbiome and differential metabolite analysis were performed using KEGG/SMP. The LPS, CSE – induced cell model was used to validate the impact of TP-TR and its active components on amino acid metabolism. The results demonstrated that TP-TR significantly improved pulmonary function, alleviated inflammation, modulated gut microbiota composition (e.g., Lactobacillus, g_ Novosphingobium), and regulated metabolic disturbances in COPD rats. Notably, amino acid metabolic pathways were consistently enriched across microbiota function prediction and untargeted metabolomic analyses of serum and lung. Targeted metabolomics further confirmed alterations in amino acid levels. Moreover, TP-TR, along with cucurbitacin B, cynaroside, glutamine, guanine, and apigenin induced alterations in the amino acid content of model cells. These findings reveal a novel mechanism by which TP-TR ameliorates COPD through gut microbiota regulation and amino acid metabolism modulation along the gut-lung axis.